Preparing of efficient social employee today: challenges and realities - Nadvychna, Tetiana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article deals with the problem of defining professional skills leading professional social sphere, the importance and complexity of his profession. Outlines the aspects to be considered in the preparation of social workers while studying at university